Applied upper-airway resistance instantly affects breath components: a unique insight into pulmonary medicine. (1st November 2017) - Sukul, Pritam; Schubert, Jochen K; Kamysek, Svend; Trefz, Phillip; Miekisch, Wolfram
Abstract: Respiratory parameters such as flow or rate have complex effects on the exhalation of volatile substances and can hamper clinical interpretation of breath biomarkers. We have investigated the effects of progressively applied upper-airway resistances on the exhalation of volatile organic compounds (VOCs) in healthy humans. We performed real-time mass-spectrometric determination of breath volatiles in 50 subjects with parallel, non-invasive hemodynamic monitoring, breath-resolved spirometry and capnometry during controlled tidal breathing (12 breaths/min). Airway resistance was increased by changing the mouthpiece diameters from 2.5 cm to 1.0 cm and to 0.5 cm. At the smallest diameter, oxygen uptake increased (35%↑). Cardiac output decreased (6%↓) but end-tidal PCO2 (8%↑) and exhalation of blood-borne isoprene (19%↑) increased. Carbon dioxide production remained constant. Furan, hydrogen sulphide mirrored isoprene. Despite lowered minute ventilation (4%↓) acetone concentrations decreased (3%↓). Exogenous acetonitrile, propionic acid, isopropanol, limonene mimicked acetone. VOC concentration changes could be modelled through substance volatility. Airway resistance-induced changes in hemodynamics, and ventilation can affect VOC exhalation and thereby interfere with breath biomarker interpretation. The effects of collateral ventilation, intra-alveolar pressure gradients and respiratory mechanics had to be considered to explain the exhalation kinetics of CO2 and VOCs. Conventional breath sampling via smaller mouthpiece diameters (≤1.0 cm, e.g. via straw in Tedlar bags or canisters, etc) will immediately affect VOC exhalation and thereby mislead the analysis of the obtained results. Endogenous isoprene may probe respiratory muscle workload under obstructive conditions. Breath-gas analysis might enhance our understanding of diagnosis and management of obstructive lung diseases in the future.